1995
DOI: 10.1108/13552549510104429
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐objective optimization of part‐ building orientation in stereolithography

Abstract: In rapid prototyping, such as SLA (stereolithography apparatus) and FDM (fused deposition modelling), the orientation of the part during fabrication is critical as it can affect part accuracy, reduce the production time, and minimize the requirement for supports and, thus, the cost of building the model. Presents a multi-objective approach for determining the optimal part-building orientation. Considers different objectives such as part accuracy and building time. Objective functions have been developed based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
149
0
1

Year Published

1998
1998
2024
2024

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 243 publications
(163 citation statements)
references
References 2 publications
3
149
0
1
Order By: Relevance
“…Given the limitation of current RP technologies, researchers have focused on optimizing process parameters such as the build orientation to ensure good RP part surface quality [2]. In fact, build orientation is critical not only for part surface quality, but also for production time, the need of support structure, and the production cost.…”
Section: Introductionmentioning
confidence: 99%
“…Given the limitation of current RP technologies, researchers have focused on optimizing process parameters such as the build orientation to ensure good RP part surface quality [2]. In fact, build orientation is critical not only for part surface quality, but also for production time, the need of support structure, and the production cost.…”
Section: Introductionmentioning
confidence: 99%
“…Cheng et al in [9] studied how fabrication accuracy, build time, and cost of a FDM process be affected by the orientation of the printing model. They showed that by optimizing the orientation of a model, the amount of supporting materials needed can be greatly reduced and thus can shorten the build time.…”
Section: Introductionmentioning
confidence: 99%
“…The same method can be used to estimate costs for all the rapid prototyping technologies available in a company by modifying the values of the coefficients to be multiplied by the relative parameters. Cheng et al, 1995 andFrank andFadel, 1995, aiming to search for the minimal cost build direction, propose a simple parametric approach which assumes build time to be proportional to the slices' number (b z /L). Xu et al, 1999, proposed a more sophisticated parametric approach which considers build time as the sum of layers' deposition time and total delay time between subsequent layers' deposition: …”
Section: The Proposed Methods For Build Time Estimationmentioning
confidence: 99%
“…Whereas prototype orientation is an assigned factor, build time must be estimated, so that the accuracy of cost evaluation depends on the accuracy of build time estimation. For this reason, many studies (Cheng et al, 1995;Frank and Fadel, 1995;Alexander et al, 1998;Majhi et al, 1998;Byun and Lee Kwan H., 2006) have been carried out regarding build time estimation problems.…”
Section: Layer Manufacturing Technology Costs' Structurementioning
confidence: 99%